Use of Nanoparticles in Tissue Engineering and Regenerative Medicine - Fathi-Achachelouei, Milad; Knopf-Marques, Helena; Ribeiro da Silva, Cristiane Evelise; Barthès, Julien; Bat, Erhan; Tezcaner, Aysen; Vrana, Nihal Engin (Frontiers in Bioengineering and Biotechnology, 2019)
Advances in nanoparticle (NP) production and demand for control over nanoscale systems have had significant impact on tissue engineering and regenerative medicine (TERM). NPs with low toxicity, contrasting agent properties, tailorable characteristics, targeted/stimuli-response delivery potential and precise control over behavior (via external stimuli such as magnetic fields) have made it possible their use for improving engineered tissues and overcoming obstacles in TERM. Functional tissue and organ replacements require a high degree of spatial and temporal control over the biological events and also their real-time monitoring. Presentation and local delivery of bioactive (growth factors, chemokines, inhibitors, cytokines, genes etc.) and contrast agents in a controlled manner are important implements to exert control over and monitor the engineered tissues. This need resulted in utilization of NP based systems in tissue engineering scaffolds for delivery of multiple growth factors, for providing contrast for imaging and also for controlling properties of the scaffolds. Depending on the application, materials, as polymers, metals, ceramics and their different composites can be utilized for production of NPs. In this review, we will cover the use of NP systems in TERM and also provide an outlook for future potential use of such systems.